Análise de falha de martelos oscilantes de desfibradores utilizados em usinas sucroalcooleiras - Sasso, Ricardo Aparecido (Universidade Federal de São Carlos, 2021)
Sugarcane mills have demanded more control of their production line, reduced loss of raw material, and a longer period before maintenance of their equipment, aiming to increase their profitability. The main station of this process is the mill responsible for crushing the sugar cane. Its components such as knives, hammers, and rollers are subject to degradation processes, mainly wear and corrosion, decreasing production efficiency and increasing the maintenance costs. This work aims to perform the failure analysis of hammers coated with weld, removed from a mill shredder after use. Through compositional characterization techniques, it was determined that the base material is a 1030 carbon steel, and the coating is a high Cr (22,2 %wt) and C (3,65 %wt) ferrous alloy. The coating showed greater resistance to abrasive wear compared to the base and reference material (410 stainless steel), it has greater hardness and hard carbides (type M7C3) that act as reinforcement and protection elements against the removal of the soft matrix material of ferrite and austenite by abrasive action. Despite the complexity of sugarcane juice, composed of chlorides, sulfides, and organic acids, the cyclic polarization curves did not show significant differences between the materials tested in this corrosive environment. The 410 stainless steel had better performance against corrosive effects, due to the complete dissolution of Cr in the solid solution, which ensured the formation of a protective passive film, which, unlike the coating, with a high content of Cr, creates carbides in excesses and interfaces depleted in Cr, representing preferential points for corrosion. The cracks in the coating allowed the penetration of the sugarcane juice, and subsequent detachment of the weld by impact, exposing the base material to abrasive wear and corrosive. Greater control during the coating preparation process and the use of a base material with greater corrosion resistance could significantly extend the life of the hammers.
Failure analysis of oscillating hammer mill used in the sugarcane industry
Keywords: Análise de falha; Aço; Martelo desfibrador; Cana-de-açúcar; Desgaste; Corrosão; Failure analysis; Shredding hammer; Sugar cane; Wear; Corrosion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA